2020
DOI: 10.1111/hel.12697
|View full text |Cite
|
Sign up to set email alerts
|

Persistent infection of Helicobacter pylori affects weight loss in obese population compared with persistent negative: A case‐control study based on healthy Chinese

Abstract: BackgroundThe relationship between Helicobacter pylori (H pylori) and body mass index (BMI) is still inconclusive. Not only the high rate of H pylori infection but also the increasing higher BMI levels are endangering Chinese today.MethodsThe aim of this research was to evaluate the association between different situations of H pylori infection and BMI values or levels in Chinese healthy population. A total of 39 091 individuals aged from 18 years to 80 years, performed healthy examination including a 13C/14C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The associations among obesity, genetics of obesity, obesity related bacteria and H. pylori infection were reported pair wisely, but their causal relationships are still largely unknown. It is reported that H. pylori persistent infection had a negative effect on the fall of BMI values in Chinese obese population 45 . This comorbidity between H. pylori infection and obesity may be caused by the pleiotropic effects of FTO and other genes.…”
Section: Discussionmentioning
confidence: 97%
“…The associations among obesity, genetics of obesity, obesity related bacteria and H. pylori infection were reported pair wisely, but their causal relationships are still largely unknown. It is reported that H. pylori persistent infection had a negative effect on the fall of BMI values in Chinese obese population 45 . This comorbidity between H. pylori infection and obesity may be caused by the pleiotropic effects of FTO and other genes.…”
Section: Discussionmentioning
confidence: 97%
“…It was inferred that the difference in prevalence rates between men and women may be affected by a variety of factors, such as different opportunity to obtain antibiotics, or stronger estrogens related immune response against infection in women, or different living habits 57 . Some studies also showed that H. pylori infection is positively correlated with higher body mass index (BMI) 57–59 . A community‐based study showed that H. pylori infection independently increased the risk of obesity (BMI ≥ 30) (adjusted OR: 1.84; 95% CI: 1.08–3.13) in Taiwanese adults under 50 years old 60 …”
Section: Discussionmentioning
confidence: 99%
“…The stone burden was calculated by the formula (0.785 × length max × width max ) introduced by the Clinical Research Office of the Endourological Society [ 8 ]. According to the standard set by the World Health Organization, a body mass index (BMI) of ≥ 28 is considered an obese patient in the Chinese population [ 9 ]. The present study was approved by the Ethics Committee of the First Affiliated Hospital of University of South China (No.202008191), in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%